A New Cadmium‐Based Pb2Cd3(PO4)2(P2O7) with Two Types of Isolated P–O Groups. Issue 9 (10th February 2019) - Chen, Wenqiang; Jing, Qun; Zhang, Qiaoqiao; Lee, Ming‐Hsien; Lu, Xuefang; Wei, Ping; Chen, Zhaohui
Abstract : Introduction transition metal with d 10 electrons and lone pair cations with large radius into phosphate systems are helpful to get new crystal structure configuration. Guided by the above method, the first lead cadmium phosphate, Pb2 Cd3 (PO4 )2 (P2 O7 ), was synthesized. Pb2 Cd3 (PO4 )2 (P2 O7 ) features a three‐dimensional (3D) structure, in which Pb(1)2 O8 dimer and Pb(2)O5 polyhedra are filled between the two‐dimensional (2D) layers, which are composed of unique [Cd6 P8 O30 ] groups. In the Pb II M II PO (M II = without or divalent metal ions) systems, the title compound is the first phosphate containing two different P–O groups simultaneously. The ratios of cation/phosphorus (C/P) and polymerization modes of P–O anions have a close relationship by many structural comparisons. Thermal analysis shows that Pb2 Cd3 (PO4 )2 (P2 O7 ) melts congruently and is thermally stable. In addition, the UV/Vis‐IR diffuse reflectance spectrum and infrared (IR) spectrum have been reported. The relationship between electronic structure and optical properties was clarified by first‐principles studies. Abstract : The crystal structure of a new cadmium‐based compound Pb2 Cd3 (PO4 )2 (P2 O7 ), containing two kinds of P–O groups, exhibits unique [Cd6 P8 O30 ]∞ layers.